An in vivo model to assess magnesium alloys and their biological effect on human bone marrow stromal cells. (December 2015) - Yoshizawa, Sayuri; Chaya, Amy; Verdelis, Kostas; Bilodeau, Elizabeth A.; Sfeir, Charles
Graphical abstract: Abstract: Magnesium (Mg) alloys have many unique qualities which make them ideal candidates for bone fixation devices, including biocompatibility and degradation in vivo . Despite a rise in Mg alloy production and research, there remains no standardized system to assess their degradation or biological effect on human stem cells in vivo . In this study, we developed a novel in vivo model to assess Mg alloys for craniofacial and orthopedic applications. Our model consists of a collagen sponge seeded with human bone marrow stromal cells (hBMSCs) around a central Mg alloy rod. These scaffolds were implanted subcutaneously in mice and analyzed after eight weeks. Alloy degradation and biological effect were determined by microcomputed tomography (microCT), histological staining, and immunohistochemistry (IHC). MicroCT showed greater volume loss for pure Mg compared to AZ31 after eight weeks in vivo . Histological analysis showed that hBMSCs were retained around the Mg implants after 8 weeks. Furthermore, immunohistochemistry showed the expression of dentin matrix protein 1 and osteopontin around both pure Mg and AZ31 with implanted hBMSCs. In addition, histological sections showed a thin mineral layer around all degrading alloys at the alloy–tissue interface. In conclusion, our data show that degrading pure Mg and AZ31 implants are cytocompatible and do not inhibit the osteogenic property of hBMSCs in vivo . These results demonstrate that this model can be used to efficiently assess the biological effect of corroding Mg alloys in vivo . Importantly, this model may be modified to accommodate additional cell types and clinical applications. Statement of Significance: Magnesium (Mg) alloys have been investigated as ideal candidates for bone fixation devices due to high biocompatibility and degradation in vivo, and there is a growing need of establishing an efficient in vivo material screening system. In this study, we assessed degradation rate and biological effect of Mg alloys by transplanting Mg alloy rod with human bone marrow stromal cells seeded on collagen sponge subcutaneously in mice. After 8 weeks, samples were analyzed by microcomputed tomography and histological staining. Our data show that degrading Mg alloys are cytocompatible and do not inhibit the osteogenic property of hBMSCs in vivo . These results demonstrate that this model can be used to efficiently assess the biological effect of corroding Mg alloys in vivo .